The Effects Capital Allocation on Financial Performance in Wamena Regency Government - Nunung Karyati; Kaharuddin; Lukman Chalid; Kartika; Basse Faradiba (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
The objectives of this study are: 1) To determine the effect of Net Profit on the allocation of capital on the financial performance of Wamena Regency, 2) To determine the effect of the Remaining Budget Calculation (SILPA) on the capital allocation on the Financial Performance of Wamena Regency, 3) To determine the effect of more influence between the remaining more calculations of Angga and Labara on the allocation of capital on the financial performance of Wamena Regency. Research on the relationship of Capital Allocation and Its Impact on Financial Performance in the Wamena Regency Government, so in this study using library research (library review) to see what should be done in managing capital allocation and its impact on performance. This research was conducted at the Regional Financial and Asset Management Agency of the Wamena Regency Government, the research period was two months. This time is used to obtain data and information from the object of research as well as other data relevant to this research, until the time to process the data to the preparation of research results.The results showed that the Net Profit and SILPA variables simultaneously had a positive and significant effect on the Analysis Affecting Capital Allocation and Its Impact on Financial Performance but not significantly on the level of Analysis Affecting Capital Allocation and Its Impact on Financial Performance in the Wamena Regency Government.